Characteristics, potential sources, and cancer risk apportionment of PM10-bound polycyclic aromatic hydrocarbons in Bengbu, Central China - Wu, Danchen; Ma, Zhijing; Diao, Haitao; Wang, Wanru; Chen, Liu; Zhou, Dalin; Yang, Jing; Zhen, Quan (Frontiers in Public Health, 2024)
Polycyclic aromatic hydrocarbons (PAHs) were measured in 342 daily PM10 samples collected in four seasons at a site in Bengbu, China. This study was a qualitative and quantitative investigation of the emission sources of atmospheric PAHs in Bengbu and the spatial distribution of regional PAH sources in PM10 samples. The annual concentrations of the 16 EPA priority PAHs ranged from 1.45 to 62.16 ng/m3, with an annual mean of 7.63 ± 7.38 ng/m3. The seasonal trends during the year were: winter (6.13–62.16 ng/m3, median = 14.99 ng/m3) > autumn (2.01–18.78 ng/m3, median = 4.90 ng/m3) > spring (1.45–19.34 ng/m3, median = 3.32 ng/m3) > summer (1.57–4.27 ng/m3, median = 2.12 ng/m3). The PAHs over the year were dominated by medium-molecular-weight PAHs (39.81%), followed by high-molecular-weight PAHs (35.77%), and low-molecular-weight PAHs (24.42%). The diagnostic ratio method and positive matrix factorization revealed that the PAH sources in Bengbu in spring and summer were industrial emissions, coal and biomass combustion, and traffic emissions; while the sources in autumn and winter were coal and biomass combustion and traffic emissions. According to a backward trajectory clustering analysis and potential source contribution function analysis, Bengbu City was mainly affected by pollution from the northern and northwestern regions in spring, autumn, and winter, while it was more affected by the coastal monsoon in summer. The PAH pollution in Bengbu was most severe in spring, autumn, and winter, and the health risk to the population was also most severe at that time. The health risk to adult males (3.35 × 10−4) was greater than the risk to adult females (3.14 × 10−4), and the health risk to adults was greater than the risk to children (2.52 × 10−4).